Pengaruh Inflasi, Pendidikan dan Upah Terhadap Kesempatan Kerja dan Kemiskinan di Indonesia - Sinta Ariska; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to determine the extent of the effects of inflation, education, wages on employment opportunities and poverty in Indonesia. ative. This study uses data from the Central Statistics Agency in 2012-2016. Data analysis used is silmutan panel data method. The results showed that partially (1) inflation had positive and insignificant effects on poverty in Indonesia (2) education had a negative and significant effect on poverty in Indonesia (3) wages had a negative and insignificant effect on poverty in Indonesia (4) influential employment opportunities positive and insignificant towards poverty in Indonesia (5) inflation has a positive and insignificant effect on employment opportunities in Indonesia (6) education has a negative and insignificant effect on employment opportunities in Indonesia (7) wages have a negative and insignificant effect on employment opportunities in Indonesia .